FIQIH DAN PERMASALAHAN KONTEMPORER - Hilal, Syamsul (Universitas Islam Negeri Raden Intan Lampung, 2012)
Abstak: Fiqh is understood literally or understanding of body and evolving in a community of mankind. In conjunction with the religion of Islam, the word connotes in an effort Fiqh Muslims -are represented among scholars explore - and practice the teachings of his religion based on the Koran and the Hadith as well as respond to legal issues that arise in the midst of the people with reference to the sources of Islamic law through the efforts of understanding , observation and study them on their arguments, so the existence of the Islamic community was shaded by the values of Islamic law. Intellectual heritage of Islamic jurisprudence as a creative response without the dynamics of moderen life, will ditinggalkann by the wheel of life history that continues to rotate, move forward, leaving the backwardness, decline and stagnation. For that, the necessary breakthrough creative and progressive thinking to make jurisprudence as a discipline that can provide a major contribution in the midst of a dynamic world civilization, science and technology challenges, globalization, industrialization and moderenization. In the face of contemporary legal problems, usage of the methodology of ushuliyah is a non-negotiable. Kata kunci: Fiqih, Klasik dan Kontemporer (Islamic Law, Clasic and Contemporer)